(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Adolescent idiopathic scoliosis (AIS) is a three-dimensional spinal deformity often associated with postural misalignment, pain, and reduced quality of life. While conventional exercises are commonly prescribed, scoliosis-specific methods such as the Schroth Method may offer greater therapeutic benefits. Objective: To compare the effectiveness of the Schroth Method versus conventional exercise in improving posture and reducing pain in adolescents with AIS. Methods: This randomized controlled trial (RCT) was conducted under the CONSORT guidelines over a six-month period, from April to October 2024, at Hayatabad Medical Complex (HMC-MTI), Peshawar. In this randomized controlled trial, adolescents aged 10–18 years with a Cobb angle of 10°–30° were allocated to either a Schroth-based exercise program or a conventional exercise group for 12 weeks. Primary outcomes included craniovertebral angle, thoracic kyphotic angle, and Numeric Pain Rating Scale scores. Secondary outcomes included Cobb angle, angle of trunk rotation, SRS-22 scores, and balance parameters. Measurements were taken at baseline, 6, 12, and 24 weeks. Results: The Schroth group showed significantly greater improvements in postural alignment, Cobb angle reduction, and pain scores compared to the conventional group (p < 0.05). Improvements were sustained at 24-week follow-up. Conclusion: The Schroth Method demonstrated superior effectiveness over conventional exercises in managing posture and pain in AIS. Incorporating scoliosis-specific exercise into conservative management may enhance patient outcomes.